Neither Pet, Nor Working Dog : the Proximity and Distance of Qimmiit (Dogs) in Inuit Families of the Central Canadian Arctic before the Creation of Settlements - Francis Lévesque (Enfances, Familles, Générations, 2019)
Research Framework: The situation of disability entails one or more forms of dependency of the disabled person vis-à-vis his entourage or professionals. Caregivers, family members, are then solicited in a more or less recurrent way to accompany the person in activities that cannot be done alone. Facilitated by "care" or "caring for others" practices, special ties, different from ordinary relationships, are formed as a result, particularly with parents. This type of relationship based on dependency questions Western family models that tend to favour the elective links between individuals, responding to a movement of autonomization of individuals and a priority set on affection. The disabled person is then caught between two opposing forces: the need to rely on the help of relatives and / or external persons or institutions and the desire to be more autonomous or as autonomous as a non-disabled person. It is precisely between these two forces that animal assistance intervenes, and more precisely the guide dog. As a living being, the guide dog will provide daily support to his handler who will allow him to take on a different role vis-à-vis other members of the family.Objectives: The objective of this exploratory survey is to identify the avenues of research around this theme of animal assistance. Indeed, the gain of autonomy with respect to the family and the relief that this may represent for third-party caregivers transform intra-family relations initially modified by disability. At the same time, a relationship of affection is created with the animal which gives the dog a special place within the family. The dog does not have a status of simple pets and is not an ordinary care worker either. It is therefore necessary to understand the consequences of animal assistance on the way in which the disabled person occupies his / her roles within the family and to clarify the transformations of the place of the dog in contemporary Western societies based on the status of the guide dog within the handler family. ...